Is electrodermal testing as effective as skin prick tests for diagnosing allergies? A double blind, randomised block design study. Issue 7279 (20th January 2001) - Lewith, George T; Kenyon, Julian N; Broomfield, Jackie; Prescott, Philip; Goddard, Jonathan; Holgate, Stephen T
Abstract: Objective: To evaluate whether electrodermal testing for environmental allergies can distinguish between volunteers who had previously reacted positively on skin prick tests for allergy to house dust mite or cat dander and volunteers who had reacted negatively to both allergens. Design: Double blind, randomised block design. Setting: A general practice in southern England. Participants: 15 volunteers who had a positive result and 15 volunteers who had a negative result on a previous skin prick test for allergy to house dust mite or cat dander. Intervention: Each participant was tested with 6 items by each of 3 operators of the Vegatest electrodermal testing device in 3 separate sessions (a total of 54 tests per participant). For each participant the 54 items comprised 18 samples each of house dust mite, cat dander, and distilled water, though these were randomly allocated among the operators in each session. A research nurse sat with the participant and operator in all sessions to ensure blinding and adherence to the protocol and to record the outcome of each test. Outcome: The presence or absence of an allergy according to the standard protocol for electrodermal testing. Results: All the non-atopic participants completed all 3 testing sessions (810 individual tests); 774 (95.5%) of the individual tests conducted on the atopic participants complied with the testing protocol. The results of the electrodermal tests did not correlate with those of the skin prick tests. Electrodermal testing could not distinguish between atopic and non-atopic participants. No operator of the Vegatest device was better than any other, and no single participant's atopic status was consistently correctly diagnosed. Conclusion: Electrodermal testing cannot be used to diagnose environmental allergies.